Analisis Respon Mahasiswa Terhadap Media Animasi Matakuliah Geografi Pariwisata - Rizky Nur Hakimah; Ellyn Normelani; Rendya Adi Kurniawan (JPG (Jurnal Pendidikan Geografi), 2023)
Experts have verified animation media, a learning medium about the potential of regional tourism as a medium for teaching tourism Geography courses, and was declared feasible to be used as a learning medium and has been tested, but the student response to the use of the media has not been studied. The method used in this study uses a quantitative descriptive research method that analyzes student responses to animation media in the tourism geography course as many as 35 students (small class) in the Geography study program, Faculty of Social and Political Sciences, Lambung Mangkurat University. The questionnaire instrument uses Google forms, the analysis uses percentages. The results of the study describe the average of student responses to answer agree to all indicators of 96.42% and those who answer disagree by 3.58%, based on the data obtained it can be concluded that animated media is easy to use and can be well received by students as user.